2010
DOI: 10.1016/j.gie.2010.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of narrow-band imaging and pit pattern analysis significantly improved for less-experienced endoscopists after an expanded training program

Abstract: Using high-magnification NBI increased the differential diagnostic skill of the LEE group after expanded training so that it was equivalent to that of the HEE group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 40 publications
7
86
0
1
Order By: Relevance
“…Related to this problem, a recent study has reported outcomes of training in NBI magnification. This study revealed that an hour-long training lecture could increase the differential diagnostic skills of inexperienced NBImagnification operators to expert levels [24]. Properly conducted short training in FICE magnification performed at our institution potentially offers the same effectiveness as that reported for NBI.…”
Section: Discussionmentioning
confidence: 60%
“…Related to this problem, a recent study has reported outcomes of training in NBI magnification. This study revealed that an hour-long training lecture could increase the differential diagnostic skills of inexperienced NBImagnification operators to expert levels [24]. Properly conducted short training in FICE magnification performed at our institution potentially offers the same effectiveness as that reported for NBI.…”
Section: Discussionmentioning
confidence: 60%
“…Recent studies have reported outcomes of training in NBI with magnification. These studies revealed that a 20-60 min training lecture could increase the differential diagnostic skills of operators inexperienced in NBI with magnification to expert levels [28,29]. Short training courses in FICE with magnification properly conducted in our institution potentially offer the same effectiveness.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, it requires considerable experience to use ME-NBI for diagnosis of gastric cancer. Studies have shown that advanced training can improve the diagnostic rate of early gastric cancer [31,32]. Therefore, the differences in the experience level of the endoscopists among the studies included may also be a factor contributing to heterogeneity.…”
Section: Discussionmentioning
confidence: 99%